The role of labor unions in the mobilisation against violence and harassment at work in the public sector in Mali and Senegal - (:unkn) unknown (My University, 2023)
Panel Hist25 : « The African labour movement at a historical crossroads: past and future of unionism, work and society in Africa. » The International Labour Conference (ILC) adopted the Violence and Harassment Convention (No. 190) and its accompanying Recommendation (No. 206) in 2019. These two instruments that have been built with active participation of unions, are the first international labour standards to provide a common framework to prevent, combat and eliminate violence and harassment in the professional work, including gender-based violence and harassment. While the number of African countries that have ratified the Convention is still very low, the international multidisciplinary research team (members coming from law, sociology, anthropology and gender studies; from Mali, Senegal and France) presenting this communication is analysing which stakeholders are involved in the prevention of violence and harassment, in security and care for suvivors and in relevant public policy. The case studies from Mali and in Senegal focus on the public sector, with its supposedly exemplary role. The object is to identify who are the principal actors mobilized, how they interact and what are their strategies and methods, and the results obtained. Based on data from semi-structured interviews with key actors in 4 ministries in each country, and from an online survey of the ministries’ staff, particular emphasis will be placed on the role that the labor unions in both countries play in fighting harassment and violence at work in the public sector and also concerning advocacy about Convention 190 in Senegal and Mali.
Keywords: African Research